Clinical Outcome After Surgical Treatment of Traumatic Peroneal Nerve Injury: An Analysis of Risk Factors After Different Surgical Approaches - Daniel N. Werkmann; Ute M. Bäzner; Martin Petkov; Lena Minzenmay; Gregor Durner; Gregor Antoniadis; Christian R. Wirtz; Maria T. Pedro; Andreas Knoll; Andrej Pala (Neurology International)
Background: This study aims to analyze potential risk factors that may influence the clinical outcomes following surgical treatment of traumatic peroneal nerve lesions. Methods: We conducted a retrospective analysis of patients with traumatic peroneal nerve injuries treated with decompression, split repair, or nerve grafting between 2010 and 2020. Motor function and potential risk factors were evaluated. Results: Out of 93 patients, 42 (45%) underwent decompression, 15 (16%) received split repair, and 36 (39%) required autologous nerve grafting. Up to one year after surgery, weakness of the anterior tibial muscle improved from a median of M0 to M3. After one year following nerve decompression, functional recovery was observed in 28 (65%) cases, in 9 (21%) cases after split repair, and in 7 (16%) cases following autologous nerve grafting. A defect greater than 8 cm was associated with significantly poorer improvement of extensor hallucis longus (p = 0.037, HR 0.109). We found no significant associations between age, diabetes mellitus, arterial hypertension, obesity, and postoperative outcomes. Conclusions: According to the present data, a significant number of patients achieved functional improvement following surgical treatment, indicating that this procedure should be considered an important treatment option in selected cases.